PRINCIPAL MANAGERIAL LEADERSHIP AND TEACHER DISCIPLINE GOVERNANCE: A COMPARATIVE STUDY OF ISLAMIC AND PUBLIC PRIMARY SCHOOLS - Sholehuddin Sholehuddin; Fauzan Fauzan; Muhamad Hasby Putroanto; Dien Nurmarina Malik Fadjar; Salsabila Anita Firdaus (PD PGMI se Indonesia, 2026)
This study aims to examine the managerial leadership of school principals in enforcing teacher discipline at Islamic and public primary schools. Using a qualitative descriptive-comparative approach, this study was conducted at MIS Al-Hidayah and SDN Kampung Bulak 02 in South Tangerang. The participants consisted of 12 informants, including principals, vice principals, school committee members, and teachers selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and were analyzed using Miles and Huberman’s interactive model through data collection, data reduction, data display, and conclusion drawing. The findings show that the principals performed seven interrelated managerial roles: evaluator, manager, administrator, supervisor, leader, innovator, and motivator. Both principals demonstrated exemplary leadership as the main basis for building teachers’ collective awareness of discipline. However, MIS Al-Hidayah showed a more structured discipline governance system through fingerprint attendance, weekly and monthly evaluations, integrity pacts, and direct follow-up mechanisms. In contrast, SDN Kampung Bulak 02 relied more on personal communication, collaborative discussion, manual attendance records, and direct reprimands. The study concludes that teacher discipline enforcement becomes more sustainable when exemplary leadership is supported by accurate administrative data, routine evaluation, systematic supervision, and technology-based monitoring. These findings contribute to educational leadership and school management studies by integrating leadership influence, managerial functions, and discipline governance in the context of Indonesian primary education.